2015
DOI: 10.14257/ijca.2015.8.5.35
|View full text |Cite
|
Sign up to set email alerts
|

Joint Torque Control of Hydraulic Quadruped Robot

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…To avoid the interference of asynchronous motion, the attention will be paid to the position of a servo actuator with electro-hydraulic in its control mode. According to the related research in the reference [23][24][25][26], as shown in Eq. ( 1), the transfer function expression of the single-cylinder servo system with an electro-hydraulic position should be derived:…”
Section: Modeling Of a Servo Actuator With Electro-hydraulicmentioning
confidence: 99%
“…To avoid the interference of asynchronous motion, the attention will be paid to the position of a servo actuator with electro-hydraulic in its control mode. According to the related research in the reference [23][24][25][26], as shown in Eq. ( 1), the transfer function expression of the single-cylinder servo system with an electro-hydraulic position should be derived:…”
Section: Modeling Of a Servo Actuator With Electro-hydraulicmentioning
confidence: 99%
“…In order to avoid movement interference, the position of actuator should be taken into account in the driving force control mode. According to the works of Wang et al, 16 Shao et al, 17 Gong et al 18 and Zhang et al, 19 the transfer function of single cylinder electro-hydraulic position servo system can be obtained, as shown in the following equation…”
Section: Electro-hydraulic Servo Actuator Modellingmentioning
confidence: 99%
“…The integration of both electronic and hydraulic equipment that absorbed both advantages is extensively used nowadays. Due to the ability to create a large force, torques, and high energy density, EHA system becomes widely used in robotic, mobile machine, metal forming, and manufacturing, [1][2][3][4]. The dynamic sources such as electric motor or engine drives provide hydraulic pump dynamics that deliver fluid under pressure.…”
Section: Introductionmentioning
confidence: 99%